2021
DOI: 10.1016/j.omtn.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

MAFG-driven osteosarcoma cell progression is inhibited by a novel miRNA miR-4660

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy in the adolescent population. MAFG (v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog G) forms a heterodimer with Nrf2 (NF-E2-related factor 2), binding to antioxidant response element (ARE), which is required for Nrf2 signaling activation. We found that MAFG mRNA and protein expression is significantly elevated in human OS tissues as well as in established and primary human OS cells. In human OS cells, MAGF silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…To confirm the bioinformatics observation, we examined POLRMT expression in local human OS tissues. OS tumor tissues (“T”) and surrounding normal bone tissues (“N”) were derived from a total of eleven ( n = 11) primary OS patients [ 19 ]. qRT-PCR assay results, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To confirm the bioinformatics observation, we examined POLRMT expression in local human OS tissues. OS tumor tissues (“T”) and surrounding normal bone tissues (“N”) were derived from a total of eleven ( n = 11) primary OS patients [ 19 ]. qRT-PCR assay results, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1F ) and protein (Fig. 1G ) levels in established OS cell lines (U2OS and MG63) and primary human OS cells (pOS-1 and pOS-2, derived from two different patients [ 19 ]) were significantly higher than those in the primary human osteoblasts (“Ob”) (Fig. 1F, G ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of v-maf musculoaponeurotic fibrosarcoma oncogene family protein G (MAFG) and v-maf musculoaponeurotic fibrosarcoma oncogene family protein F (MAFF) are now known as proliferation and differentiation coactivators acting in cooperation with NFE2L2 in the mouse hepatoma cell line Hepa1c1c7 (Hepa1) via the Keap1-NFE2L2 pathway [30], and the protein MAFG acts in cooperation with NFE2L2 (Nrf2) to transcriptionally govern either repressive or activating gene functions in antioxidant response element (ARE)-dependent antioxidant pathways in skeletal muscle cells [31]. The protein MAFG is also involved in bile acid homeostasis [32], liver cancer [33], osteosarcoma [34], and central nervous system inflammation [35]. Von Scheidt M et al [36] demonstrated that MAFF is a novel central regulator of an atherosclerosis-relevant liver network and that MAFF can trigger context-specific expression of LDLR and other genes known to affect coronary artery disease risk.…”
Section: Comparison With Other Relevant Studies and Deductions From Major Resultsmentioning
confidence: 99%